Country-level impact of global recession and China's stimulus package: A general equilibrium assessment - Diao, Xinshen; Zhang, Yumei; Chen, Kevin Z. (International Food Policy Research Institute, 2010)
A dynamic computable general equilibrium model is developed to assess the impact of the recent global recession and the Chinese government's stimulus package on China's economic growth. The model is first used to capture the actual sector-level economic growth in 2008 and the possible economic performance in 2009 without the intervention of the Chinese government through its stimulus package. Under this global recession scenario, the GDP growth rate in 2009 falls to 2.9 percent mainly as a result of the sharp drop in exports of manufactured goods, while the agricultural sector is more crisis-resilient. Because export-oriented manufacturing sectors are often import-intensive, the weakened economy is accompanied by a reduction in Chinese firms' import demand for materials, intermediates, and capital goods. The model also shows that without government intervention, the negative effect of a one-year shock on the Chinese economy would last for many years. Also, over the next five to six years, China is unlikely to replicate its strong economic performance of the past two decades.